Monograph - Ware, Chris 1967- (Rizzoli New York, 2017)
"A flabbergasting experiment in publishing hubris, [this book] charts the art and literary world's increasing tolerance for the language of the empathetic doodle directly through the work of one of its most esthetically constipated practitioners. For thirty years, writer and artist (i.e. cartoonist) Chris Ware (b. 1967) has been testing the patience of readers and fine art fans with his complicated and difficult-to-comprehend picture stories in the pages of The New Yorker, The New York Times and other charitable periodicals-- to say nothing of challenging the walls of the MCA Chicago and the Whitney Museum of American Art with his unevocative delineations and diagrams. Arranged chronologically with all thoughtful critical and contemporary discussion common to the art book genre jettisoned in favor of Mr. Ware's unchecked anecdotes and unscrupulous personal asides, the author-as-subject has nonetheless tried as clearly and convivially as possible to provide a contrite, companionable guide to an otherwise unnavigable jumble of product spanning his days as a pale magnet for athletic upperclassmen's' ire up to his contemporary life as a stay-at-home dad and agoraphobic graphic novelist. Shrewdly selected personal photos distract from justifiably little-seen early experiments littered among never-before-seen paintings and sculptures, all padded out with high-quality scans of original artwork publicizing jottings, mistakes, blunders and, especially, Mr. Ware's University juvenilia via which the reader can track a general cultural increase in tolerance for quality's decline since his work first came on "the scene." Expensive, heavy, and fashioned from the finest uncoated paper and soy-based ink, this thigh-crushing book is certain to cut off the circulation of all but the most active of comics boosters"--Amazon.com
Keywords: Ware, Chris -- 1967-; Ware, Chris / 1967- / Comic books, strips, etc; Cartoonists / United States / Biography; Comic books, strips, etc / United States; Ware, Chris / 1967-; Cartoonists; Comic books, strips, etc; United States; Autobiographies; Biography; Bildband